2022
DOI: 10.3389/fdgth.2022.817810
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Digital Health Strategies in 10 Countries With Young Populations: Do They Serve the Health and Wellbeing of Children and Youth in a Digital Age?

Abstract: Children and youth merit special attention from digital health policymakers and practitioners because of the great potential for digital transformations to both enhance and undermine their health and wellbeing. However, an analysis of digital health strategies from 10 African countries with young populations suggest that national approaches to digital health are overlooking young people's specific health needs and unique risks in relation to digital technologies and data. To better serve the needs of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…A diverse range of stakeholders has played a role in the creation and implementation of DHP services so far. This includes entities like the private sector (composed of health and wellness startups, as well as technology companies with primary operations outside the health sector), research institutions and academia, health ministries and government bodies and non-governmental organizations and foundations ( Hampshire et al ., 2015 ; Barron et al ., 2018 ; Pillay and Motsoaledi, 2018 ; Holst et al ., 2021 ; Mehl et al ., 2021 ; Holly et al ., 2022 ).…”
Section: Part 1: Advantages and Barriers For Young People In Adopting...mentioning
confidence: 99%
“…A diverse range of stakeholders has played a role in the creation and implementation of DHP services so far. This includes entities like the private sector (composed of health and wellness startups, as well as technology companies with primary operations outside the health sector), research institutions and academia, health ministries and government bodies and non-governmental organizations and foundations ( Hampshire et al ., 2015 ; Barron et al ., 2018 ; Pillay and Motsoaledi, 2018 ; Holst et al ., 2021 ; Mehl et al ., 2021 ; Holly et al ., 2022 ).…”
Section: Part 1: Advantages and Barriers For Young People In Adopting...mentioning
confidence: 99%
“…However, it is worth highlighting that although effectiveness in intervention outcomes appeared similar between studies incorporating co-design versus those that did not, previous research has found interventions that have not been tailored to disadvantaged populations are associated with poor engagement and impact, and may contribute to greater health inequalities (Coupe et al, 2018). Co-design facilitates incorporation of the intended audience's experiences and perspectives into an intervention, and informs the type of content, delivery method, and key components to ensure its accessibility (Holly et al, 2022;World Health Organization, 2020). The importance of incorporating co-design into future interventions should be considered to adequately address the unique barriers disadvantaged adolescents experience and deliver effective and appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…WHO recommends countries to actively work towards universal health coverage (UHC), and hence, investments in digital health technologies should go beyond vertical disease programs to help strengthen the overall healthcare system. Resilient governance, stewardship, health systems, and societies are all important for wide-scale deployment of digital health technologies through the lens of UHC 16,17,[58][59][60] . Resource-limited countries may initially start with high-burden diseases using tailored digital health technologies within existing resources.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on these debates and recognizing the critical role Africa is playing in global health targets and the global economy, there is a dearth of robust information about the ecological facets of digital health interventions in Africa. Important studies and policy insights inform the extent to which digital health interventions have been implemented in Africa and the barriers for the success or lack thereof [17][18][19][20][21][22][23] . Full adoption and implementation of digital health technologies in Africa require more training, access to better devices and infrastructure, and more investigations on emerging technologies including artificial intelligence, wearable devices, and big data to provide robust evidence of their potential in Africa 12,15 .…”
Section: Introductionmentioning
confidence: 99%